Do Goal-Free Problems with Guided Questions Affect Retention, Transfer, and Cognitive Load? - Aprillia, Fika; Retnowati, Endah (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study aimed to examine the effects of problem presentation and guided questions on students’ retention, transfer, and cognitive load. The study used a 2×2 factorial design with two factors: problem presentation (goal-free vs. goal given) and guided questions (with vs. without). The subjects consisted of 150 seventh-grade students from a public junior high school in Sleman Regency, who were randomly assigned to four experimental groups. The instruction was carried out in three phases: introduction, acquisition, and testing. Data were analyzed using two-way ANOVA at a significance level of 0.05. The results showed that problem presentation did not have a significant effect on retention and transfer but had a significant effect on cognitive load. Guided questions did not have a significant effect on any of the dependent variables. A significant interaction was found between problem presentation and guided questions on retention, transfer, and cognitive load in the retention test. Goal-given problems were more effective without guided questions for improving retention and transfer, while guided questions were more effective when combined with goal-free problems. Cognitive load on the retention test was higher for goal given problems with guided questions because goal given problems and guided questions led to means-end analysis and deep information processing.